2017
DOI: 10.3109/13668250.2017.1388913
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life of persons with profound intellectual and multiple disabilities: A narrative literature review of concepts, assessment methods and assessors

Abstract: Background: The objective of this study was to provide an overview of concepts, methods of assessment and assessors in empirical studies on quality of life (QoL) of persons with Profound Intellectual and Multiple Disabilities (PIMD). Method: A narrative literature review was conducted by searching electronic databases until December 2016, and the included studies were then analysed thematically. Results: Twenty-one articles were included in the analysis. Multidimensional concepts of QoL consisting of both subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
22
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 38 publications
2
22
1
Order By: Relevance
“…On the contrary, other domains were not mentioned by our interviewees, for example: self-determination, social inclusion and rights (Schalock et al, 2008). The physical cluster with elements of physical state and health is described in all combinations of domains that we found in the literature (Nieuwenhuijse et al, 2017). Our findings are also in line with the findings described by Zaal-Schuller, et al, (2018).…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…On the contrary, other domains were not mentioned by our interviewees, for example: self-determination, social inclusion and rights (Schalock et al, 2008). The physical cluster with elements of physical state and health is described in all combinations of domains that we found in the literature (Nieuwenhuijse et al, 2017). Our findings are also in line with the findings described by Zaal-Schuller, et al, (2018).…”
Section: Discussionsupporting
confidence: 90%
“…In the literature, QoL is frequently described in domains. In a literature review, we found several combinations of domains (Nieuwenhuijse et al, 2017). In our present study, the clustering of elements was an inductive process, based on interviews with seven physicians.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations